Haematological Alterations and CD4+ Count in Patients with Mycobacterium tuberculosis and HIV coinfection in Adamawa, Nigeria - James Hamuel Doughari; Isaiac Kadala; Fatima Hamza (Microbes, Infection and Chemotherapy)
Objective: Tuberculosis remains a significant public health concern as a communicable disease. This study investigated CD4+ counts and hematological parameters in patients infected with Mycobacterium tuberculosis. Methods: M. tuberculosis detection was performed using GeneXpert MTB/RIF, while CD4+ counts and hematological parameters were analyzed using BD FACS Count and SYSMEX, respectively. Results: Mycobacterium tuberculosis strain L-form, M. tuberculosis strain H83, and M. tuberculosis strain bj were identified in all hospitals surveyed. The mean CD4+ count was significantly lower in M. tuberculosis-positive patients (521.4 ± 2.3) compared to the healthy control group (936 ± 0.43) (p < 0.05). Conversely, infected patients exhibited significantly higher mean leukocyte (18.3 ± 1.03 × 109/L, p = 0.001) and erythrocyte sedimentation rate (98.6 ± 21.00 mm/hr, p = 0.002) compared to controls (4.2 ± 06.3 × 109/L and 8.7 ± 2.10 mm/hr, respectively). Mean hemoglobin levels were lower in infected patients (8.6 ± 2.30) than in controls (15.3 ± 0.01), whereas the mean platelet count was significantly higher in infected patients (602.1 ± 2.70, p = 0.001) compared to the control group (312 ± 2.02). Conclusion: A baseline assessment of immunohematological parameters should be conducted in all M. tuberculosis-positive patients before initiating anti-TB therapy. Additionally, public health education on reducing exposure to TB risk factors is essential.